(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Education occupies a pivotal role in any society and has turned out to be a basic human right under many international and national legal frameworks including the Constitution of India. Imparting more quality education is equated with a more civilized society. Keeping pace with the ever-changing society in the technology-driven globalized world, the manner of imparting education has witnessed a paradigm shift from the physical face-to-face education system to technology driven mode of education. Especially during the worst time of Covid-19 pandemic situations throughout the whole world many restrictions including long term lockdowns, curfews, and other limitations on the movement of the people were imposed leading towards impossibility in imparting physical education and in such scenario the only available, reliable and suitable medium of education was online education done through modern electronic gadgets